2002
DOI: 10.1046/j.1365-2036.2002.01145.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical mononitrate treatment in patients with anal fissure

Abstract: Aim: To assess the efficacy and patient compliance of topical mononitrate hydrogel for the treatment of anal fissure. Materials and methods: Nineteen patients with symptomatic chronic anal fissures were randomly allocated to receive either active (10 patients) or placebo (nine patients) gel treatment. Rectal administration of hydrogel containing 0.2% isosorbide‐5‐mononitrate was prescribed. Patients were instructed on its application to the anal canal twice daily for 3 weeks. A questionnaire was used to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 13 publications
0
3
0
2
Order By: Relevance
“…La recherche bibliographique a retrouvé deux méta-analyses sur le traitement chirurgical [1] et sur le traitement médical [2], sept essais randomisés comparant différents type de traitement médical et non inclus dans la méta-analyse [3][4][5][6][7][8][9], et deux études de cohorte sur les résultats à long-terme de la chirurgie [10,11]. Les deux méta-analyses [1,2] (ainsi que l'analyse détaillée sur les données des essais inclus) montrent que la sphinctérotomie interne a été comparée aux dérivés nitrés dans quatre essais et à la toxine botulique dans un essai.…”
Section: Quel Option Thérapeutique ?unclassified
See 1 more Smart Citation
“…La recherche bibliographique a retrouvé deux méta-analyses sur le traitement chirurgical [1] et sur le traitement médical [2], sept essais randomisés comparant différents type de traitement médical et non inclus dans la méta-analyse [3][4][5][6][7][8][9], et deux études de cohorte sur les résultats à long-terme de la chirurgie [10,11]. Les deux méta-analyses [1,2] (ainsi que l'analyse détaillée sur les données des essais inclus) montrent que la sphinctérotomie interne a été comparée aux dérivés nitrés dans quatre essais et à la toxine botulique dans un essai.…”
Section: Quel Option Thérapeutique ?unclassified
“…Le taux de récidive à moyen terme atteint selon les études 30-50 %. Les résultats des essais randomisés récents [4,5] rejoignent ceux de ma méta-analyse [2].…”
Section: Quel Traitement Médical De Première Intention ?unclassified
“…Isosorbide mononitrate (ISMN) is another nitrate derivative, which is also considered as a candidate for the topical fissure treatment. It was reported that the topical application of ISMN facilitated the healing of chronic fissure producing fewer side effects [8]. However, the question about the suitable drug delivery formulation has not been discussed.…”
Section: Introductionmentioning
confidence: 99%
“…1 The etiology remains controversial, but chronic constipation, anodermal ischemia, and hypertonicity of the internal anal sphincter (IAS) have all been implicated. 2,3 In recent years various substances such as glycerol trinitrate, diltiazem hydrochloride, botulinum toxin, and bethanechol have all been used for the treatment of chronic anal fi ssure.…”
Section: Introductionmentioning
confidence: 99%